A lightweight framework for dynamic GUI data verification based on scripts. (6th May 2015) - Mateo Navarro, Pedro Luis; Ruiz, Diego Sevilla; Pérez, Gregorio Martínez
Summary: Runtime verification (RV) provides essential mechanisms to enhance software robustness and prevent malfunction. However, RV often entails complex and formal processes that could be avoided in scenarios in which only invariants or simple safety properties are verified, for example, when verifying input data in Graphical User Interfaces (GUIs). This paper describes S‐DAVER, a lightweight framework aimed at supporting separate data verification in GUIs. All the verification processes are encapsulated in an independent layer and then transparently integrated into an application. The verification rules are specified in separate files and written in interpreted languages to be changed/reloaded at runtime without recompilation. Superimposed visual feedback is used to assist developers during the testing stage and to improve the experience of users during execution. S‐DAVER provides a lightweight, easy‐to‐integrate and dynamic verification framework for GUI data. It is an integral part of the development, testing and execution stages. An implementation of S‐DAVER was successfully integrated into existing open‐source applications, with promising results. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Script‐based DAta VERification framework (S‐DAVER) provides a lightweight, easy‐to‐integrate, dynamic, and automatic verification framework for Graphical User Interface data. All verification processes are encapsulated in an independent verification layer. These processes are transparent to developers. The verification rules are specified in separate files and written using general purpose, interpreted languages. Rules can be changed/reloaded at runtime without recompilation. Superimposed visual feedback is used to assist developers during the testing stage, as well as to improve users' experience during execution.